Mentoring model in LATAM for women in stem, lessons learned from design to implementation (LACCEI, 2024)
The current demand for professionals in STEM areas, aligned with the Sustainable Development Goals, specifically gender equity, has moved higher education institutions to generate initiatives that increase the presence of women in STEM areas from their education to the workplace. Gender gaps are still present in Latin American countries, and it is more visible in STEM areas. This is why the Matilda Chair was formed in an alliance between universities, which seeks to make this situation visible but also to reduce the gap with initiatives such as Mentoring Programs. The objective is to share the case study of the design and implementation of the model as a mentoring program, from the perspective of mentors, mentees and the process itself, with a qualitative methodology, considering the lessons learned during its development. This seeks to support other institutions interested in promoting and strengthening the STEM vocations of women in all stages of their lives, mainly during their education. The findings inspire us to continue with these initiatives because of the impact on the lives of all involved, those who seek to inspire, guide and motivate, and those who seek that guidance that empowers them in their decision making and development in STEM careers.